Investigation on the failure mechanism and safety mechanical-thermal boundary of a multi-disc clutch. (September 2019) - Yu, Liang; Ma, Biao; Chen, Man; Li, Heyan; Liu, Jikai; Li, Mingyang
Abstract: The comprehensive fault diagnosis method has been developed to analyze the failure of the multi-disc clutch. The mechanical buckling model is developed to investigate the relationship between the resistance torque and the periodic circumferential bright spots. The contact pressure and temperature on the friction surfaces are obtained with the consideration of the concentrated reactive load of the circlip. The friction and wear characteristics of the friction disc under different temperature conditions are explored by the pin-on-disc test, and then the surface morphologies of tested discs are observed by the metalloscope. The results demonstrate that both the thermal buckling and the mechanical buckling can result in the mechanical-thermal buckling. As the temperature varies from 15 °C to 400 °C, the disc experiences the abrasive wear, ploughing wear, adhesive wear and delamination wear in order. Finally, the mechanical-thermal safety boundaries are proposed. Moreover, the paper provides some suggestions for better design of clutch: the circlip should be optimized to avoid stress concentration; the teeth number of separate plates should be increased to improve the torque transmission capacity; the thickness of separate plates should be different which can be determined by their axial positions in the clutch pack. Highlights: The model for circumferential mechanical buckling is presented and validated. The comprehensive fault diagnosis method of the multi-disc clutch is developed. The effect of temperature on the friction and wear characteristics of a disc is studied. The safety mechanical-thermal boundary of the clutch is proposed and validated. The thickness of separate plate should be varied according to its axial position.